2007
DOI: 10.1111/j.1528-3585.2007.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Cuban Missile Crisis: Crossing Time and Space in Virtual Reality

Abstract: The Cold War is now ancient history to most university students. They can learn the facts of this period, but the feelings associated with the experience are beyond the scope of social science. Such feelings should be part of teaching and learning about international studies. Instructors can present history and politics, but without an emotional sense of empathy, students will never fully understand the subtle complexity of international affairs. They must be able to view the world from different perspectives,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…The one group I did not include in this study that some research in the past has recommended is a control group (Stover 2007). Although I considered this addition, I could not see the pedagogical value (for this group of undergraduate students) in simply spending more time with lecture and discussion on this topic, nor did I want any students to miss out on this active-learning opportunity.…”
Section: My Studymentioning
confidence: 97%
See 1 more Smart Citation
“…The one group I did not include in this study that some research in the past has recommended is a control group (Stover 2007). Although I considered this addition, I could not see the pedagogical value (for this group of undergraduate students) in simply spending more time with lecture and discussion on this topic, nor did I want any students to miss out on this active-learning opportunity.…”
Section: My Studymentioning
confidence: 97%
“…Some of these early studies provided scant evidence for enhanced learning through simulations or games, as opposed to traditional methods of teaching, even as they revealed increased student interest in the subject matter explored by these newer methods (Petranek, Corey, and Black 1992, 175). Today, however, the vast majority of studies reveal significant achievements in learning through games, simulations, and other types of active learning (Brown Games and Simulations 401 and King 2000;Enterline and Jepsen 2009;Smith and Boyer 1996;Stover 2007). As Youde describes, studies have shown that ''students retain more information, gain a deeper understanding of an issue (though this may come at the expense of breadth), examine issues from a wider range of perspectives, and generally report having more fun in class' ' (2008, 348).…”
Section: Scholarship On Teaching and Learningmentioning
confidence: 98%
“…Clema and Kirkham proposed yet a model of risks, costs and benefits in political conflicts [58]. Curiously, as late as 2007 there was a paper published on simulating the Cuban missile crisis [59]. However, this paper explores mechanistic modeling as a method of teaching history, rather than the mechanisms of the decision making process itself.…”
Section: Political Sciencementioning
confidence: 99%
“…Some works argue even this number is too conservative (Cohen 1990). Stover (2007) uses similar techniques to us with a smaller sample size of 32.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Students are more likely to retain knowledge through activities that combine doing and saying rather than through other types of learning activities such as hearing, reading, or even doing and saying separately (Boyer et al 2000). Games can demonstrate how theories "work," illustrate how institutions function, and get students to understand the emotions of actors in situations which are alien to them (Asal 2005;Stover 2007). Finally, politics makes the most sense if experienced or "played" rather than just discussed (Asal and Blake 2006).…”
mentioning
confidence: 99%